Pengaruh Pajak Daerah, Retribusi Daerah, Dana Alokasi Umum dan Dana Alokasi Khusus Pada Belanja Modal Provinsi Bali - Sudika, I Komang; Budiartha, I Ketut (E-Jurnal Akuntansi, 2017)
The purpose of this study was to determine  effect of local taxes, levies, general allocation fund, and special allocation funds on capital expenditure of Bali. This study includes 8 kabupatan and 1 city in 2010-2014. A nalysis techniques used in this research is multiple linear regression to the data of observation as much as 45. The results of study showed that the local tax  general allocation fund and special allocation funds significant positive effect on capital spending, only levies no effect on capital spending. This shows that there is still the dependence of local governments to transfer funds from the central government. T he determinant coefficient showed 87.5 percent Capital expenditures can be explained or influenced by the Local Taxes, Levies, General Allocation Fund and Special Allocation Fund while remaining 12.5 percent is explained or influenced by other variables outside our model